2015
DOI: 10.1177/0021909615595992
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Inconsistent Condom Use among Sexually Active Youths: Implications for Human Immunodeficiency Virus and Sexual Risk Behaviours in Malawi

Abstract: This study examines the risk associated with inconsistent use of condoms as a risk factor for human immunodeficiency virus/sexually transmitted infections (HIV/STIs) and sexual risk behaviours. The Malawi Demographic Health Survey 2010 data were used. Out of a sample of 2987 males and 9559 females aged 15-24 years, 511 males and 675 females were filtered in the present study. A Chi square test and logistic regression techniques were performed. About 147(28.7%) males and 240(35.6%) females reported inconsistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
(34 reference statements)
1
15
0
Order By: Relevance
“…Risky sexual behaviours which are defined as behaviours that increase the risk of transmission of sexually transmitted infections (STIs) and HIV continue to be wide spread in sub-Saharan Africa and it explains why HIV is now endemic in this region (Chialepeh and Susuman 2015). These behaviours include early age at sexual debut, having multiple sexual partners, unprotected sex with strangers, sex with partners whose STI status is unknown and when one or one's sexual partner has a STI (Agarwal et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Risky sexual behaviours which are defined as behaviours that increase the risk of transmission of sexually transmitted infections (STIs) and HIV continue to be wide spread in sub-Saharan Africa and it explains why HIV is now endemic in this region (Chialepeh and Susuman 2015). These behaviours include early age at sexual debut, having multiple sexual partners, unprotected sex with strangers, sex with partners whose STI status is unknown and when one or one's sexual partner has a STI (Agarwal et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Risky sexual behaviours are those which increase the chances of contracting sexually transmitted infections (STIs) and experiencing unintended pregnancies. [1][2][3] In Nigeria, study has confirmed that such behaviours are associated with young people like early debut in sexual activities, sex with many partners, low and inconsistent use of condoms and indulgence in unsafe sexual practices. 4 These are influenced by individual level factors and the key among these is the reason for engaging in risky sexual activities in marriage.…”
Section: Introductionmentioning
confidence: 93%
“…Some study ndings suggest that condom failure results from improper use while other studied have reported condom failures occurring through breakages or slippages which are deliberately caused by clients [13][14][15][16]. A study conducted in Mombasa, Kenya on action taken by FSWs after experiencing condom failure reported that FSWs had mixed options following these incidences: few singled out emergency contraceptives, several sought health care services and the majority did not know what do or where to go for assistance [1,2].…”
Section: Introductionmentioning
confidence: 99%